2007
DOI: 10.1002/mnfr.200600204
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase induction by cyanidin‐3‐O‐β‐glucoside in cultured human endothelial cells

Abstract: The aim of the present research was to investigate the effect of cyanidin-3-O-b-glucoside (C3G) on heme oxygenase-1 (HO-1), endothelial nitric oxide synthase (eNOS), inducible NOS (iNOS) and dimethylarginine dimethylamino hydrolase-2 (DDAH-2) expression in cultured endothelial cells. Different concentrations (0.00625 -250 lM) of C3G were tested in order to investigate possible beneficial and harmful effects of C3G. Our data demonstrated that C3G increased the induction of eNOS and HO-1 in a dose-dependent mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 50 publications
4
26
0
Order By: Relevance
“…The antioxidant properties of anthocyanins, and especially of the C3G, depend on their radical scavenging and inhibitory effects on lipid peroxidation [2, 47] by their strong oxygen radical absorbance capacity (ORAC) and nitric oxide (NO) and cyclooxygenase inhibitory activities [4850] (Table 3). Given the unstable nature of anthocyanins under natural conditions, it was believed that such molecules would not have antioxidant activity in living systems but many studies, instead, have demonstrated the antioxidant activity of C3G also in in vivo experiments [51].…”
Section: Components Of Red Orangementioning
confidence: 99%
“…The antioxidant properties of anthocyanins, and especially of the C3G, depend on their radical scavenging and inhibitory effects on lipid peroxidation [2, 47] by their strong oxygen radical absorbance capacity (ORAC) and nitric oxide (NO) and cyclooxygenase inhibitory activities [4850] (Table 3). Given the unstable nature of anthocyanins under natural conditions, it was believed that such molecules would not have antioxidant activity in living systems but many studies, instead, have demonstrated the antioxidant activity of C3G also in in vivo experiments [51].…”
Section: Components Of Red Orangementioning
confidence: 99%
“…It is important to underline that the effects of ACNs and PAs are not limited to the modulation of inflammation. These compounds have been demonstrated to affect several functions directly or indirectly related to endothelial function and inflammation such as oxidative stress, capillary permeability, platelet aggregation, thrombus formation, nitric oxide production, and atherogenesis . In this regard, we recently documented that certain ACNs and the PA rich fraction (RF) were able to counteract lipid accumulation in macrophages derived from monocytic THP‐1 cells; however, when considering the single compounds, the effects were concentration and compound dependent .…”
Section: Introductionmentioning
confidence: 99%
“…Recent study suggests that lipid-lowering fibrates and insulin-sensitizing thiazolidinediones can be used as potential therapeutics since these drugs induce HO-1 expression via activation of peroxisome proliferator-activated receptor-a (136). Besides the aforementioned drugs, naturally occurring polyphenols are also able to induce HO-1 expression (242,252), suggesting that a considerable part of the protective effects of fruit consumption against cardiovascular diseases could be mediated through HO-1 pathway.…”
Section: Ho-1 In Regulation Of Vascular Biologymentioning
confidence: 99%